ANALISIS FONDASI HOLISTIK DALAM MASA TRANSISI ANAK USIA DINI KE SEKOLAH DASAR DI KOTA BANDUNG - Fawazillah, Anjeli; Nurdin (Fakultas Tarbiyah Universitas Ibrahimy Situbondo, 2025)
A holistic foundation during the transition from early childhood to primary school is a critical period that significantly influences children's overall development. This study aims to explore the impact of this transition on children's religious, social, emotional aspects, positive learning attitudes, motor skills, and cognitive abilities. The primary method employed is a qualitative approach using questionnaires distributed to 23 parents of children aged 5 to 8 years. The findings indicate that children have demonstrated the presence of their holistic foundations. However, several areas still require further attention and guidance from both parents and educators. Therefore, collaboration among educational institutions, teachers, and parents must be well-aligned to ensure a smooth transition from early childhood to primary education.